If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7(y-8)+24=-27(y-6)
We simplify the equation to the form, which is simple to understand
7(y-8)+24=-27(y-6)
Reorder the terms in parentheses
+(+7y-56)+24=-27*(y-6)
Remove unnecessary parentheses
+7y-56+24=-27+*(+y-6+)
Reorder the terms in parentheses
+7y-56+24=+(-27y+162)
Remove unnecessary parentheses
+7y-56+24=-27y+162
We move all terms containing y to the left and all other terms to the right.
+7y+27y=+162+56-24
We simplify left and right side of the equation.
+34y=+194
We divide both sides of the equation by 34 to get y.
y=5.7058823529412
| -5p=-8p+3p | | -2x-(4+x)=2 | | n=-70 | | (5x+10)+(6x)=180 | | -6(x-8)=-54 | | -9(c+1)=5 | | 3.(x-2)=2x-4 | | 3a-24= | | 7y-32=-27y-6 | | 43-(3x+9)=3(x+2)+x | | 2.89+a=17.10 | | -2x-(4x)=2 | | 3-n=-n-1+4 | | .5x+.33x-.2(x+3)=.1 | | 4+2x+3x=1 | | x^2-x+5=9 | | 6x-10=89+7x | | -s^3+8= | | 45+5x=8x | | n+6=n+6 | | 4x+7+8x=-17 | | 8y-16=32 | | y-4=2y+2-7y | | -3+z=-9 | | 25.12=.33(12.56H) | | x^2+10x+9=y | | 5(x-1)+13(2x+3)=3(2x-7)-x | | 10x+14=11x+3 | | 2x-11=5x+6 | | 4g-2+1=g-6+3g | | 6(i+2j)+8j-16j= | | 4(n+7)+8(n+9)= |